Sosialisasi Pendidikan Politik Bagi Masyarakat Petani dan Nelayan di Kabupaten Konawe Kepulauan - Kasim, Syaifuddin Suhri; Laxmi; Asriani; Taufik; Sultrayansa; Iwan; Fallz, Irvon (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2024)
The aim of this community service is to provide knowledge and understanding regarding political education as a learning process for the community in Konawe Islands Regency. Through the dissemination of political education for farming and fishing communities in Konawe Kepualaun Regency, this activity is considered very effective in providing political education related to legal policies in the form of threats to perpetrators and recipients of money, especially in general elections. The results of implementing this activity created an active and focused discussion due to the participation of the community who were willing to give their time and presence to participate as participants in community service activities in Konawe Islands Regency. In this discussion, the aim of this activity is to find out the public's knowledge regarding legal policies, as well as providing an opportunity for the public to convey their hopes and realities in accepting legal policies in Konawe Islands Regency. Thus, the results of the discussion in this activity show that public knowledge regarding legal policies in the Konawe Islands Regency is still very lacking, this is due to the lack of information that the public has regarding this matter. Therefore, it is hoped that this service activity will continue and requires evaluation in order to improve political education for the community in Konawe Islands Regency.